SYNTHESIS OF p-METHOXY-CYNNAMIL- p-METOXYCINAMATE FROM ETHYL p-METHOXYCINAMAT WAS ISOLATED FROM DRIED RHIZOME Kaempferia Galanga L AS SUNSCREEN COMPOUND - Titik Taufikkurohmah (Indonesian Journal of Chemistry, 2005)
Synthesis of p-methoxy-cynnamil-p-methoxy-cinnamate, (PMS)2O from ethyl-p-methoxy-cinnamate (EPMS) from dry rhizome of kaempferia galanga L as sunscreen compound have been done. Isolation of EPMS was done by percholation using ethanol 96 % and recrystallitation using methanol to have 2.2 % yield. Hydrolysis of EPMS using alcoholic KOH resulted methoxycinnamic acid (APMS) of 90.26 % yield. Reduction EPMS using lithium aluminium hydride in dry ether would give p-methoxycinnamoyl alcohol (PMS-OH) of 41.98 % yield. Then reaction of p-methoxycinnamoyl chloride (PMS-Cl) and PMS-OH in chloroform would produce p-methoxycinnamoyl p-methoxycinnamate ((PMS)2O) of 1.77 % yield. All compound were identified by TLC and several spectrometry methodes i.e. U.V Vis, IR, 1H-NMR and GC-MS.